Martajasah Mangrove Ecotourism Development Strategy, Bangkalan Regency, Madura - Akhmad Farid; Hotimatus Zahroh; Teti Sugiarti (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
Ecotourism is one of the ecological-based tourism activities, one of which is mangrove ecotourism. Martajasah is one of the mangrove ecotourism areas that have a high potential to be developed because it is adjacent to religious and culinary tourism. The purpose of this study is to determine the profile of tourists and to determine the development strategy of Martajasah Mangrove Ecotourism, Bangkalan Regency. The analytical method used in this study is Importance Performance Analysis (IPA). This analysis relates the level of importance of an attribute owned by a particular object with the reality (performance) felt by tourists. Based on the results of the study, it can be concluded that the majority of Martajasah Mangrove Ecotourism tourists come from Bangkalan Regency, male with student status, with an average age of 16-25 years. The biggest motivation for tourists to visit Martajasah Mangrove Ecotourism is for recreation. The development strategy of Martajasah Mangrove Ecotourism is to improve the quality and quantity of white sand, increase the length of the beach, increase the availability of travel agents to make it easier for tourists to go to Martajasah Mangrove Ecotourism and increase the number of facilities and infrastructure at the Martajasah Mangrove Ecotourism location.